The impact of enterprise resource planning (ERP) on the operational and managerial effectiveness of an organization: a case study at Telekom Malaysia / Noor'aini Ismail - Ismail, Noor'aini (2017)
The enterprise resource planning (ERP) system is known to be a robust system and is in high demand in Malaysia. With its capabilities to integrate all the core modules like Procurement, Finance, Accounting and Human Resources, this system is able to fulfill all the companies' requirements to have a centralized system which can manage all the operational and managerial tasks in the organisation. This can be seen in the industrial sector such as the telecomunications industries, which are taking a high risk in implementing this system while expecting positive effects to their organisation. Considering the perks that organizations may enjoy, such as better customer satisfaction, improved information accuracy and improved decision-making for the top management, this robust system has become among the most risky investments for an organization. The goal of this study is to investigate the factors which most contribute to the effectiveness of the ERP system by employing five constructs from seven of DeLone and McLean's Updated IS Success Model (2003). The factors are information quality, system quality, service quality, user satisfaction and net benefits. This quantitative study illustrates the experiences of end users from various departments with various privileges in the headquarters of the telecommunication organization. A survey method was conducted to understand the relationship between the constructs and effectiveness of the ERP system. The findings indicate the significant impact of service quality to the net benefits, in both models of with or without mediating factors. While information quality and service quality shows not significant to the net benefits with or without mediating factors. The effectiveness of the system depends solely on user satisfaction. Since ERP system implementation is considered risky to any organization, the reliability of the system and its service are very much depending on the perceptions on the end-users. From the perspectives of business requirements, today's business experts are as well very much relying on tools in supporting them generating revenue for the organization. Hence, IT governance should play their roles for an actionable strategy to improvise the ERP system in the organization and so forth crafting the acceptable fashion of using the system effectively organization itself.